2003
DOI: 10.1046/j.1526-4637.2003.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

Physician Variability in the Management of Acute Postoperative and Cancer Pain: A Quantitative Analysis of the Michigan Experience

Abstract: A B S T R A C TBackground. Little is known about physician attitudes, goals, or satisfaction regarding acute postoperative and cancer pain management.Objectives. To provide quantitative data regarding the status of acute postoperative and cancer pain management by Michigan physicians. To measure physician confidence, preference, and satisfaction as well as identify their pain care goals for acute postoperative and cancer pain management. To evaluate variability in acute postoperative and cancer pain decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 57 publications
3
35
0
1
Order By: Relevance
“…However, the complex nature of pain management and limited information about patient characteristics might also limit the ability to appropriately and reliably predict pain treatment outcomes for the population at large. [31][32][33][34]78 Few studies have attempted to address the effects of pain cross-culturally, across the age continuum, or included the experiences of both women and men. 8,38,51 In addressing the complex nature of chronic pain management, there is a paucity of empirical research on the physical, social, and behavioral factors that might influence chronic pain outcomes, pain characteristics, and pain management in an ethnically diverse population.…”
mentioning
confidence: 99%
“…However, the complex nature of pain management and limited information about patient characteristics might also limit the ability to appropriately and reliably predict pain treatment outcomes for the population at large. [31][32][33][34]78 Few studies have attempted to address the effects of pain cross-culturally, across the age continuum, or included the experiences of both women and men. 8,38,51 In addressing the complex nature of chronic pain management, there is a paucity of empirical research on the physical, social, and behavioral factors that might influence chronic pain outcomes, pain characteristics, and pain management in an ethnically diverse population.…”
mentioning
confidence: 99%
“…Indeed, relative to non-Hispanic whites, African Americans report higher levels of pain and disability associated with several pain conditions[1;3;24-28;67;68;82], including post-operative pain[29;43;53]. In addition, multiple studies have demonstrated greater experimental pain sensitivity among African Americans [6;7;17;30;59-61;69].…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that healthcare providers – nurses in particular – are prone to underestimate the severity of patient pain compared to self-report, and that there is variability in pain ratings between and within provider types (Choiniere et al, 1990; Davoudi et al, 2008; Green et al, 2001; Green and Wheeler, 2003; Luger et al, 2003; Sloman et al, 2005). Relatively little has been published concerning the accuracy of nurses’ assessment of patient emotional status in general and in the context of pain in particular.…”
Section: Introductionmentioning
confidence: 99%